Enantioselective copper(II)‐catalyzed Henry reaction utilizing chiral aziridinyl alcohols. (27th October 2014) - Wang, Xiaojuan; Zhao, Wenxian; Li, Gaowei; Wang, Jin; Liu, Guanjun; Liu, Lantao; Zhao, Ruijuan; Wang, Mincan
<x xml:space="preserve">Abstract</x> A family of enantiopure β‐aminoalcohols based on aziridine backbones were synthesized, and examined as chiral ligands for the copper(II)‐catalyzed asymmetric Henry reaction of aromatic aldehydes with nitromethane, giving β‐nitroalcohols in excellent yields (up to 93%) and moderate to good enantioselectivities (up to 82%). Moreover, possible transition states of the reaction are proposed. Copyright © 2014 John Wiley & Sons, Ltd.